Teaching and Researching Autonomy - Benson, Phil (Longman Pearson, 2011)
Appropriate for third year and above students, lecturers and researchers in applied linguistics. Also of interest to language teachers and researchers involved in autonomous learning, self-access, and learner training, and the TESOL market in general. This book is the first to offer a comprehensive account of autonomy in language learning and the educational practices associated with the concept. It details the history and sources of the concept of autonomy, discusses areas of debate concerning its definition and reviews research on theoretical and practical application